Systematic Review of Research Trends in Engineering Team Performance. Issue 1 (2nd January 2023) - Hindiyeh, Ramy I.; Ocloo, William K.; Cross, Jennifer A.
Abstract: The ever-increasing demand for more complex products and services has led to an increased need for engineering teams. Despite this increase, available literature on engineering team performance factors is limited, and the trend in this research field is not clear. This Systematic Literature Review (SLR) aims at identifying research trends and gaps in engineering team performance. Three reputable research platforms were used. The SLR found that the most studied engineering team performance factor is the impact of skillset or knowledge of individual team members. The paper gives engineering managers insight into team management decision making and identifies several opportunities for future research.